2019
DOI: 10.24325/issn.2446-5763.v5i14p36-52
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Satisfação Acadêmica, Expectativa De Futuro E Motivação Acadêmica Em Estudantes De Graduação Do Instituto Federal De Rondônia Campus Ariquemes

Abstract: No sistema de ensino os profissionais buscam a identificação de fatores que contribuem para a obtenção do sucesso escolar e profissional. Neste sentido, o estudo teve como objetivo avaliar a satisfação acadêmica, expectativa de futuro e a motivação acadêmica dos alunos dos cursos de graduação do Instituto Federal de Rondônia - Campus Ariquemes. Participaram da pesquisa 79 estudantes, com média de idade de 26,06 anos (s = 9,316), variando de 17 a 58 anos. Na distribuição por sexos, 36,7% dos respondentes (29 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Based on what was previously presented, it can be concluded that research hypothesis 1 was fully validated, since the IMS value obtained was 3.91 (0.71), allowing us to infer that students are slightly satisfied with the institution. The results that confirm the research hypothesis 1 are in accordance with the results of other authors [20,25,26] who, despite finding statistical evidence that students are slightly satisfied with the institution, point out that the perception of the lack of infrastructure resources (physical environment, e.g., library and laboratories) and gaps in the teaching infrastructure (faculty, e.g., stimulating and challenging classes) have a negative impact on student satisfaction, which is also true for the present investigation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Based on what was previously presented, it can be concluded that research hypothesis 1 was fully validated, since the IMS value obtained was 3.91 (0.71), allowing us to infer that students are slightly satisfied with the institution. The results that confirm the research hypothesis 1 are in accordance with the results of other authors [20,25,26] who, despite finding statistical evidence that students are slightly satisfied with the institution, point out that the perception of the lack of infrastructure resources (physical environment, e.g., library and laboratories) and gaps in the teaching infrastructure (faculty, e.g., stimulating and challenging classes) have a negative impact on student satisfaction, which is also true for the present investigation.…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained in the present investigation provide an important practical contribution to the monitoring and management of student satisfaction by educational institutions since it presents an indicator that reflects how satisfaction is presented, serving as a parameter for fault corrections and the implementation of potential improvements that increase the satisfaction and achievement of students, thereby increasing their chances of staying and their success in the institution. As theoretical contributions, we emphasize the fact that the results obtained in the present investigation confirm the findings of other authors [20,25,26] who specifically studied the Federal Education Network, making it clear that although students are satisfied with the institution, factors such as access to adequate infrastructure, stimulating faculty, and educational environment are of paramount importance for increasing student satisfaction. In addition, the results found in the present investigation are in line with other investigations carried out in other countries, such as the United Kingdom, Romania, and Portugal [7][8][9][10].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations